Convergent total synthesis of (±) myricanol, a cyclic natural diarylheptanoid. Issue 45 (9th November 2018) - Bochicchio, A.; Schiavo, L.; Chiummiento, L.; Lupattelli, P.; Funicello, M.; Hanquet, G.; Choppin, S.; Colobert, F.
Abstract : Third total synthesis of the meta, meta -bridged diarylheptanoid: myricanol with remarkable anti-tau properties. Abstract : Myricanol1, a constituent of Myrica species, has been reported to lower the levels of the microtubule-associated protein tau (MAPT), whose accumulation plays an important role in some neurodegenerative diseases, such as Alzheimer's disease (AD). Herein we described a new synthetic route to prepare myricanol in 9 steps and 4.9% overall yield starting from commercially available 2, 3-dimethoxyphenol and methyl 3-(4-benzyloxyphenyl)propanoate. The key steps are a cross-metathesis to obtain a linear diarylheptanoid intermediate and a Suzuki–Miyaura domino reaction to generate the challenging macrocycle.